Caring of Disabilities Deaf Mute Patient with Talking Devices Application Based on Mobile - Afrian Nuari, Nian; Halim, Paisal; Badruddin, Syamsiah; Maulamin, Taufan; Ikhsan Setiawan, Muhammad; Widayati, Dhina; Sofyana STT, Latjuba; Abdullah, Dahlan (International Journal of Engineering and Technology, 2018)
The role of nurses in children with difable is to help in communicating so they can interact with others. Deaf mute requires health care and information on health education.This research focused on an application that facilitates Disabilities Deaf Mute Patient to communicate with other by using a mobile phone. This application based on mobile user by typing letters and it will automatically change into the form of voice (text to speech) that have been arranged into a word so can understood by the other person who use the application. This research helps nurses to communicate by using talking tools application. Development of systems using mobile technology by using Java programming language and talking tool. Results of this study was an application of learning system that helps teachers to communicate with their mute children. The application of mute children will be greatly helped in communicating with the interlocutor.Â Â